(untitled) (Research, Society and Development, 2022)
Bacteria from the genus Bacillus sp. have a high potential for the biological control of phytopathogenic fungi. Therefore, in the present research we proposed to evaluate the antagonistic capacity of Bacillus sp. isolates against the phytopathogenic fungus Sclerotium sp. The tests were performed using two methods (dual and modified dual), also using five Bacillus sp. isolates (LBM01, LBM02, LBM03, LBM04 and LBM06). Mycelial growth evaluations were performed on BDA culture medium. All experiments were performed in triplicate and the plates were incubated under a 12 h photoperiod at 28±1 ºC for 7 days. Radial growth of the pathogens was measured at the intervals of 24, 48, 72, 96, 120, 144 and 168 h. The percentage of inhibition was calculated using the equation: I% = [(C-T)/C]x100. All Bacillus sp. isolates tested were able to inhibit the mycelial growth of Sclerotium sp. within 72 h, while isolates LBM01, LBM03 and LBM06 were able to maintain inhibition for 168 h. The isolate LBM06 showed the highest percentage of inhibition in all two culture methods used.